Trifluoperazine induced blepharospasm: a case report - Dhiman, Indu; Dhiman, Umesh; Sharma, Tarun; Sharma, Aradhna (International Journal of Advances in Medicine, 2017)
We hereby report an unusual case of trifluoperazine (typical antipsychotic drug) induced tardive blephrospasm which was relieved subsequently after dechallenging the drug. Thereafter patient was started with clozapine (atypical antipsychotic drug). This possibility of blepharospasm should always be kept in mind while prescribing trifluoperazine.